PENGEMBANGAN INDUSTRI HALAL MELALUI E-COMMERCE PADA SEKTOR FASHION MUSLIM NDONESIA - Purnomo, Weka Arum; Prawiro, Atmo; Haniatunnisa, Siti (Sekolah Tinggi Ilmu Fikih Syeikh Nawawi Tanara Serang, 2023)
Indonesia's development into a world halal industry in the field of Muslim fashion continues to increase as Indonesia's Muslim population reaches 87%. The aim of the research is to determine the potential for developing the halal e-commerce industry in Indonesia. The results of the research are that halal e-commerce can be a solution to encourage the development of the halal industry, with the availability of halal e-commerce making it easier for producers to transact and market their products online. The SWOT analysis shows that halal e-commerce in the Muslim fashion sector to encourage the development of the halal industry in Indonesia is found from internal factors, the strength of the number of influencers and artists who wear Muslim fashion, the number of internet users, teenagers and children. For internal factors, it was found that the majority of Indonesia's population is 87% Muslim, awareness of Muslims dressing according to Islamic law. The threat of many competing countries, the lack of uniformity of internationally agreed halal certificates, the minimal level of knowledge about the market for MSME players means that many still sell offline.